Graphene‐Based Planar Microsupercapacitors: Recent Advances and Future Challenges. Issue 1 (18th October 2018) - Liang, Jiaxing; Mondal, Anjon Kumar; Wang, Da‐Wei; Iacopi, Francesca
Abstract: The continuous development of integrated electronics such as maintenance‐free biosensors, remote and mobile environmental sensors, wearable personal electronics, nanorobotics etc. and their continued miniaturization has led to an increasing demand for miniaturized energy storage units. Microsupercapacitors with graphene electrodes hold great promise as miniaturized, integrated power sources thanks to their fast charge/discharge rates, superior power performance, and long cycling stability. In addition, planar interdigitated electrodes also have the capability to reduce ion diffusion distances leading to a greatly improved electrochemical performance. Either as standalone power sources or complementing energy harvesting units, it is expected that graphene‐based microsupercapacitors will play a key role as miniaturized power sources in electronic microsystems. This review highlights the recent development, challenges, and perspectives in this area, with an emphasis on the link between material and geometry design of planar graphene‐based electrodes and their electrochemical performance and integrability. Abstract : An analysis of the recent advances in graphene‐based microsupercapacitors is provided herein. There is an increasing interest in miniaturized power sources. Graphenic carbon is proven to be a high‐performance active material. Further advances are expected from the control of the pore structure of the material, the tailoring of porosity to the electrolyte and the use of hybrid material combinations.